Rheological properties of calcium silicate‐filled isotactic polypropylene - Maiti, S. N.; Singh, Gurunam; Ibrahim, Mohd. Nordin (Wiley, 2002)
The melt rheological behavior of calcium silicate‐filled isotactic polypropylene, with filler volume contents of 0–17.8%, was determined at 493 K. The composites followed the power law in shear stress versus shear rate variations and were shear thinning. Initially, apparent melt viscosity decreased until a critical filler volume content of 8.5% was reached. However, on further increase in calcium silicate concentration, apparent melt viscosity increased. Melt elasticity also showed an initial decrease until 8.5% filler content was reached and then an increase beyond this filler content. Surface treatment of calcium silicate with a titanate coupling agent, LICA 38, modified the rheological properties because of the plasticizing/lubricating effect of LICA 38.